2008
DOI: 10.1016/j.ympev.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory algorithm to identify intra-host recombinant viral sequences

Abstract: Since recombination leads to the generation of mosaic genomes that violate the assumption of traditional phylogenetic methods that sequence evolution can be accurately described by a single tree, results and conclusions based on phylogenetic analysis of data sets including recombinant sequences can be severely misleading. Many methods are able to adequately detect recombination between diverse sequences, for example between different HIV-1 subtypes. More problematic is the identification of recombinants among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…The expectation was that UDPS would therefore reveal a more populous set of recombinants. Retrospective analysis of HIV data sets has demonstrated that recombinants which were previously overlooked can be identified by use of the NNet algorithm in conjunction with the PHI statistic (36,47). Our analysis supports this observation and demonstrates the suitability of our strategy to the study of HCV UDPS data.…”
Section: Discussionsupporting
confidence: 76%
“…The expectation was that UDPS would therefore reveal a more populous set of recombinants. Retrospective analysis of HIV data sets has demonstrated that recombinants which were previously overlooked can be identified by use of the NNet algorithm in conjunction with the PHI statistic (36,47). Our analysis supports this observation and demonstrates the suitability of our strategy to the study of HCV UDPS data.…”
Section: Discussionsupporting
confidence: 76%
“…Recombination analysis was carried out for sequence populations in each tissue and in each macaque using three methods, as previously described (51): (i) GARD (52), (ii) an algorithm that uses split decomposition networks in combination with the "phitest" (53,54) implemented in Splitstree4 software (55) calibrated specifically to identify likely recombinants within intrahost viral populations (53,56,57), and (iii) Recombine (58). Recombinant sequences were also identified using bootscanning, implemented in Simplot (59) and RDP (60), with observed trends similar to those obtained with the algorithms listed above (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the large number of insertions and deletions that are typically problematic to align, a portion of the highly variable gp120 V1 domain (SIVmm239 positions 6987 to 7035) was removed. All nef and gp120 sequences were tested for recombination using the PHI test implemented in Splitstree4 (40), as previously described (41,42), and suspected recombinants were removed prior to distance and phylogenetic analyses. All alignments are available upon request.…”
Section: Methodsmentioning
confidence: 99%